2005
DOI: 10.1103/physreve.72.027103
|View full text |Cite
|
Sign up to set email alerts
|

Restoring site percolation on damaged square lattices

Abstract: Restoring site percolation on a damaged square lattice with the nearest neighbor (N2) is investigated using two different strategies. In the first one, a density y of new sites are created on the empty sites with longer range links, either next-nearest neighbor (N3) or next-next-nearest neighbor (N4), but without N2. In the second one, new longer range links N3 or N4 are added to N2 but only for a fraction v of the remaining non-destroyed sites. Starting at p(c)(N2), with a density x of randomly destroyed site… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…The calculated thresholds p c are 0.1372(1), 0.1420(1), 0.0976(1), 0.1991(1), 0.1036(1), 0.2455(1) for (NN + 2NN), (NN + 3NN), (NN + 2NN + 3NN), 2NN, (2NN + 3NN), 3NN neighbourhoods, respectively. In contrast to the results obtained for a square lattice [13][14][15] the calculated percolation thresholds decrease monotonically with the site coordination number z, at least for our inspected neighbourhoods. Fig.…”
Section: Introductioncontrasting
confidence: 99%
“…The calculated thresholds p c are 0.1372(1), 0.1420(1), 0.0976(1), 0.1991(1), 0.1036(1), 0.2455(1) for (NN + 2NN), (NN + 3NN), (NN + 2NN + 3NN), 2NN, (2NN + 3NN), 3NN neighbourhoods, respectively. In contrast to the results obtained for a square lattice [13][14][15] the calculated percolation thresholds decrease monotonically with the site coordination number z, at least for our inspected neighbourhoods. Fig.…”
Section: Introductioncontrasting
confidence: 99%
“…The quantity is based on the coordination zone ζ, the sites number z and the sites distances r to the central site in the neighbourhood. The dependency of p c on this newly proposed index ξ follows roughly a power law with an exponent close to −0.705 (23).…”
Section: Introductionmentioning
confidence: 83%
“…The percolation thresholds were initially estimated for nearest neighbour interactions [17,18] but later also complex (or extended) neighbourhoods were studied for 2D (square [19][20][21][22][23][24][25], triangular [19,20,26,27], honeycomb [19]), 3D (simple cubic [25,28,29]) and 4D (simple hypercubic [30]) lattices.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that these results may be applicable to a model of constrained percolation [38]. Malarz and coworkers [39][40][41][42][43][44][45][46] carried out extensive numerical simulations on lattices with combinations of "complex neighborhoods" in two, three, and four dimensions. Koza and collaborators [25,26] studied percolation of overlapping shapes on a lattice, which can be mapped to extended-range site percolation.…”
Section: Introductionmentioning
confidence: 99%